THE INFLUENCE OF HEALTH PROMOTION ON INCREASING THE KNOWLEDGE OF MOTHERS OF TODDLERS ABOUT ROTAVIRUS IMMUNIZATION - Gultom, Desi Meliana; Supriati (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
In frame achieving the SDGs2030 target, the Indonesian Government is committed tall For protect all over public from pain, disability and death consequence diseases dangerous that can be prevented with immunization, one of them with add new antigen immunization into the immunization program national. Influencing factors​ immunization There is two that is, the encompassing factors knowledge (age, level education, occupation, number children, culture, beliefs society, and income family) and behavior (perception, motivation and attitude to health). Focus transformation of the primary health care system, namely get closer Health services through networking until level villages and hamlets, incl For strengthen promotion and prevention as well as resilience to pandemic. So study This will carried out at Posyandu Teratai 1, Ujung Padang Village, Padangsidimpuan City. With variable study Influence Health Promotion About Rotavirus immunization against Enhancement Knowledge of Mothers of Toddlers About Rotavirus with amount sample of 32 respondents. Taking sample done method taking probability sampling sample, namely technique that gives opportunity or chance The same for every element or member population For chosen become sample, and use technique accidental sampling ie made respondents when respondents present moment counseling held. Analysis done using SPSS statistical tests with using the T-Test test. Research result show that respondents who have knowledge not enough before done promotion very high health that is knowledge before done promotion health about Rotavirus immunization showed that 26 respondents (81.2%) were knowledgeable not enough. Knowledge after done promotion health obtained ata part big respondents knowledgeable Good as many as 20 respondents (62.5%), and no There is respondents (0%) who are knowledgeable not enough. There is a significant influence because p value = 0.0000 < α = 0.05 between difference knowledge public about Rotavirus immunization before and after done promotion health.